Analysis of asthma patients for cryptococcal seroreactivity in an urban German area. - Grahnert, A.; Muller, U.; von Buttlar, H.; Treudler, R.; Alber, G. (Med Mycol, 2015)
Cryptococcus neoformans is an opportunistic fungal pathogen that causes lung inflammation and meningoencephalitis in immunocompromised patients but is also able to asymptomatically infect immunocompetent individuals. C. neoformans is found ubiquitously especially in urban areas where it is spread by pigeons, and fungal exposure may predispose for asthma development already at an early age, as soon as confronted with pigeon droppings. In the study presented here, we investigated the presence of specific immunoglobulin G (IgG) against C. neoformans in sera from patients suffering from asthma in comparison to a healthy control cohort, accrued from the Leipzig Research Centre for Civilization Diseases (LIFE). For serological analysis we developed a flow cytometry (FACS) based assay specific for an acapsular strain of C. neoformans to comprehensively analyze different cryptococcal serotypes. Compared with the non-asthmatic cohort, asthmatics exhibited, as expected, an elevated level of total serum immunoglobulin E (IgE), whereas the IgG seroreactivity against C. neoformans was not significantly different among the two groups (P = .118). Nevertheless, there was a trend toward increased Cryptococcus-specific IgG antibodies in the serum of asthmatics. Additionally, in male asthmatics an increased IgG-mediated seroreactivity compared to female asthmatics was found. This points to a higher prevalence of subclinical C. neoformans infection in male asthmatics and may support the hypothesis of C. neoformans as a risk factor for the development of asthma in urban areas.
Keywords: Adult; Antibodies, Fungal/*blood; Asthma/complications/*epidemiology; Case-Control Studies; Cryptococcosis/complications/epidemiology/*immunology; Cryptococcus neoformans/*immunology; Female; Humans; Male; Middle Aged